GENDER DALAM PERSPEKTIF HUKUM ISLAM - Asasriwarni Asasriwarni (Universitas Islam Negeri Imam Bonjol Padang, 2012)
Gender is more directed to the social construction by proposing a review of the aspects of sex. When the gender issue is analyzed based on the Islamic law, so it can not be avoided its discussion although it have to refer to the provisions of Allah and the prophet based on the Qur'an and Sunnah. Based on the Islamic law, gender is a nature that must be used wthn their respective roles sustably, not to be exploited for the momentary interest or certain group. So the restrictions in an absolute man-made law should refer to the provisions of the Syari’ah. Keywords : Gender, Syari’ah and FiqhCopyright © 2012 by Kafa`ah All right reservedDOI : 10.15548/jk.v2i2.48